(untitled) (MMIT Proceedings, 2025)
The article discusses the main methods of assessing students’ knowledge, used in different historical periods of the development of pedagogical science. A comparative analysis of traditional and modern approaches to assessment has been carried out, their strengths and weaknesses have been identified. The key changes in approaches to assessing academic achievements from oral exams to a competencybased approach are presented. Special attention is paid to the influence of the socio-cultural context on the choice of assessment strategies